he Legislative Framework For The Development Of Petroleum In Malaysia: An Overview - Krishnan, A. (Journal of Malaysian and Comparative Law, 2019)
Broadly there are three categories of systems prevailing in various countries for the development of their hydrocarbons: a) general legislation system; b) ad hoc agreement; and c) a hybrid system of general legislation and individually negotiated agreements.